Childhood/Adolescent stressors and allostatic load in adulthood: Support for a calibration model. (November 2017) - Berg, Mark T.; Simons, Ronald L.; Barr, Ashley; Beach, Steven R.H.; Philibert, Robert A.
Abstract: Rationale: Past research has established an association between childhood and adolescent stressors and elevated inflammatory and metabolic biomarkers in adulthood, but questions remain about the theoretical model most suited to explain this association. Objective: This study examined alternative hypotheses from four theoretical models regarding the link between exposure to stressful early life circumstances and cumulative biological risk, or allostatic load, in adulthood. Methods: Multivariate regression models and data from a sample of 327 African American women from the Family and Community Health Study were used to test hypotheses. Results: Stressors measured during the phases of childhood and adolescence predicted increased allostatic load, irrespective of adult circumstances that might account for this effect. Also, these early stressors conditioned the health effects of adult positive and negative circumstances. Exposure to childhood and adolescent stressors amplified the effect of adult economic hardship on allostatic load and dulled the beneficial effects of positive events and high-quality relationships. Conclusion: These findings support the perspective that childhood and adolescence are phases when exposure to adversities possibly enhances vulnerability to biological risk in adulthood irrespective of later life circumstances. Also, the findings are consistent with the perspective that childhood and adolescent adversities calibrate biological risk resulting from aversive and positive features of the adult social environment. Highlights: Childhood/Adolescent stressors increase allostatic load (AL). Adult economic hardships have no effect on AL independent of early stressors. Positive adult circumstances do not appear to buffer the effects of early stressors. Childhood/Adolescent stressors moderate the effects of adult circumstances on AL.